ANALISIS DETERMINAN RASIO PEMBIAYAAN DAN BIAYA OPERASIONAL TERHADAP PROFITABILITAS PADA BANK JABAR BANTEN SYARIAH PERIODE 2017-2020 - Nurlaelah Zakiah; Ilis Solehah (Universitas Muhammadiyah Prof Dr Hamka, 2022)
The purpose of this study was to analyze the level of the financing ratio or the Financing to Deposit Ratio (FDR) and operating costs (BOPO) to the Return on Assets (ROA) that occurred in BJBS for the 2017-2020 period. The research method used is in the form of quantitative analysis. The data source is generated from the Quarterly Reports published by the BJBS official website starting from the period 2017 to 2020. The results show that partially the FDR ratio shows a value of 0.620 > 0.05 meaning that there is no significant effect between FDR on ROA, while the BOPO ratio shows a value of 0.000 <0.05 means that there is a significant effect between BOPO on ROA. Simultaneously, the resulting value of 0.000 <0.05 means that there is a significant effect between FDR and BOPO on ROA. In that case, the R-Square value obtained is 0.820 or equivalent to 82% which indicates that the effect of FDR and BOPO on ROA is 82% while the rest (100% - 82% = 18%) is influenced by other variables outside of the research discussion. Keywords; Financing to Deposit Ratio, Operational Costs, Return on Assets.